Accumulation and risk assessment of heavy metals in sediments and zoobenthos (Bellamya aeruginosa and Corbicula fluminea) from Lake Taihu - Kong, Ming; Hang, Xiaoshuai; Wang, Longmian; Yin, Hongbin; Zhang, Yimin (Water science and technology, 2016)
Accumulation and risk assessment of metals in sediments and zoobenthos (Bellamya aeruginosa and Corbicula fluminea) from Lake Taihu were studied. Results showed that metal (Cr, Cd, Cu, Zn, Pb and Ni) concentrations in Lake Taihu varied greatly, and Cd in the Zhushan Bay showed higher bioavailability compared to the other metals studied. The spatial distribution of metals in B. aeruginosa and C. fluminea was similar to that in sediments. Zn and Cu exhibited the higher mean concentration in B. aeruginosa and C. fluminea, which was in good accordance with its higher content in surrounding sediment. Labile fractions (i.e., acid-soluble (F1), reducible (F2) and F1 + F2) of Cu and Zn in sediments showed a significant positive correlation with them in B. aeruginosa (P < 0.01); no correlation relationship was found for metals (Cd, Cr, Cu, Zn, Pb and Ni) between in the tissue of C. fluminea and in sediments. The results of ecological risk assessment showed that Zhushan Bay was seriously contaminated by metal Cd, as it made the main contribution of all the metals. Total target hazard quotients indicated that adults and children both had potential health risk through consuming C. fluminea. Hazard index values suggested that adults and children might experience adverse health effects through consuming B. aeruginosa and C. fluminea.